Rational use of phosphorus on seed yield, nutrient composition and uptake in rice (Oryza sativa) - rapeseed (Brassica campestris subsp. oleifera var. toria) - greengram (Phaseolus radiatus) crop sequence - S.C. MASTHAN,; S.N. REDDY,; SHAlK MOHAMMAD,; B.VIJAY NUMAR, (Indian Journal of Agronomy, 2001)
A field investigation was carried out during 1991-92 and 1992-93 to find out the dose of phosphorus sufficient to meet the nutritional requirement of rice (Oryza sativa L.) - rapeseed [Brassica carnpestris L. ssp. oleifera (Metzger) Sinsk. var. toria] - greengram (Phaseolus radiatus L.) cropping sequence. The concentration of N and K reduced by the application of 26.2 kg Plha to rice and rapeseed in the 3 crops. The P concentration increased in rice and greengram but not in rapeseed. The uptake of N, P and K was more in rice and rapeseed fertilized with 26.2 kglha P. The residual -- effect of 13.1 or 26.2 kg P ha applied to rice also influenced the uptake of these nutrients in rapeseed. Greengram in summer removed more N, P and K due to the cumulative influence of 26.2 kglP ha through rice and rapeseed. Phosphorus @ 26.2 kglha (rabi) to rice significantly increased the yield. Its residual effect was also signifi- cant in increasing the production of rapeseed grown as second crop in winter (rabi) season. The cumulative effect of residual P throuqh the previous crop cf rice and its direct application both at 26.2 kglha P maximized the grain yield of rapeseed. The third crop of greengram in summer gave maximum yield by the residual effect of phosphorus applied to rice and rapeseed in kharif and rabi respectively.
Keywords: Cropping sequence; Rice; Rapeseed; Greengram; Nutrient up- . take; Yield